DIGITAL PLATFORMS FOR SOCIAL CONFLICT RESOLUTION AS AN ELEMENT OF PUBLIC POLICY FOR REGIONAL DEVELOPMENT - KHUDOLEI, Veronika; YANKOVOI, Roman; MASHNENKOV, Kostiantyn; TULCHINSKIY, Rostislav (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article substantiates the conceptual foundations for developing digital platforms for social conflict resolution as an integral element of modern regional development policy. It demonstrates that such platforms function as institutional infrastructures integrating citizen participation tools, online mediation, data analytics, and public accountability mechanisms into a unified governance architecture. Their application enables proactive detection of weak signals of social tension, accelerates response to emerging conflict situations, improves transparency of administrative decisions, and strengthens trust and coordination between government institutions, business actors, and civil society organisations. A comprehensive structural–logical model of the platform is proposed, reflecting the “sense–analyze–decide–act–learn” governance cycle. The model incorporates modules for early signal detection, diagnostics of conflict drivers, interactive mediation instruments, decision-making support systems, and continuous monitoring based on real-time data flows. The study emphasizes the necessity of unified data standards, SLA-based service regulation, RACI responsibility matrices, performance metrics, and ethical frameworks for data collection, storage, and algorithmic processing. The integration of these elements ensures consistency, interoperability, and accountability within platform-based conflict management processes. The article highlights the potential of digital conflict-resolution platforms to become embedded within regional strategic planning, spatial development programs, and evidence-based budgeting, thereby reducing transaction costs and enhancing coherence across public policies. Additional attention is given to risks such as digital inequality, algorithmic bias, data security vulnerabilities, and insufficient administrative capacities. Corresponding mitigation strategies include capacity-building programs, public–private partnerships, transparent audit procedures, and human-centred design principles. The study concludes that digital platforms for social conflict resolution represent an effective instrument for strengthening community resilience, fostering inclusive governance, expanding opportunities for citizen engagement, and increasing the adaptability and efficiency of regional public administration under conditions of heightened socio-economic uncertainty.